Impact of Unions on Wage Levels and Income Distribution: Comment - Gallaway, Lowell E. (Quarterly Journal of Economics, 1960)
Journal Article Impact of Unions on Wage Levels and Income Distribution: Comment Get access Lowell E. Gallaway Lowell E. Gallaway University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 74, Issue 2, May 1960, Pages 324–329, https://doi.org/10.2307/1884257 Published: 01 May 1960